THE ORDER OF THOUGHT. WITTGENSTEIN ON ARTIFICIAL INTELLIGENCE AND BRAIN-PROCESSES - Alberto Emiliani (Daimon)
This paper is not devoted to analyzing Wittgenstein´s claims about machine-thought but to clarifying and expanding an argument of Wittgenstein´s about the non-mechanicity of thought. According to my reading of Zettel 608, such a feature of thought should not be merely accounted to the contrary, it should be argued for by showing that an analysis of our brains does not provide any account of what thought consists in (a conceptual case). The point is quite radical: a neural structure does not define a concept, but a concept defines what neural (or otherwise physical) structures would answer to it. Concepts are therefore not mere "emergent properties" of neural frameworks-unless by "emergent property" we mean a property which does not proceed from its underlying substratum. On these grounds, there is no need for thought to be mechanicall at all, for the order ot thought has not to answer to a physical (or even to micro-logical) order which is mechanical in nature. The inspection of a case of vagueness is intended to ilustrate the point at issue.